Low-Dose Decitabine Augments the Activation and Anti-Tumor Immune Response of IFN-γ+ CD4+ T Cells Through Enhancing IκBα Degradation and NF-κB Activation - Li, Xiang; Dong, Liang; Liu, Jiejie; Wang, Chunmeng; Zhang, Yan; Mei, Qian; Han, Weidong; Xie, Ping; Nie, Jing (Frontiers in Cell and Developmental Biology, 2021)
Background: CD4+ T cells play multiple roles in controlling tumor growth and increasing IFN-γ+ T-helper 1 cell population could promote cell-mediated anti-tumor immune response. We have previously showed that low-dose DNA demethylating agent decitabine therapy promotes CD3+ T-cell proliferation and cytotoxicity; however, direct regulation of purified CD4+ T cells and the underlying mechanisms remain unclear. Methods: The effects of low-dose decitabine on sorted CD4+ T cells were detected both in vitro and in vivo. The activation, proliferation, intracellular cytokine production and cytolysis activity of CD4+ T cells were analyzed by FACS and DELFIA time-resolved fluorescence assays. In vivo ubiquitination assay was performed to assess protein degradation. Moreover, phosphor-p65 and IκBα levels were detected in sorted CD4+ T cells from solid tumor patients with decitabine-based therapy. Results: Low-dose decitabine treatment promoted the proliferation and activation of sorted CD4+ T cells, with increased frequency of IFN-γ+ Th1 subset and enhanced cytolytic activity in vitro and in vivo. NF-κB inhibitor, BAY 11-7082, suppressed decitabine-induced CD4+ T cell proliferation and IFN-γ production. In terms of mechanism, low-dose decitabine augmented the expression of E3 ligase β-TrCP, promoted the ubiquitination and degradation of IκBα and resulted in NF-κB activation. Notably, we observed that in vitro low-dose decitabine treatment induced NF-κB activation in CD4+ T cells from patients with a response to decitabine-primed chemotherapy rather than those without a response. Conclusion: These data suggest that low-dose decitabine potentiates CD4+ T cell anti-tumor immunity through enhancing IκBα degradation and therefore NF-κB activation and IFN-γ production.